Prospective Plant Based Anticancer Lead Molecules - Kaur, Prabhjot; Sharma, Vikas (Current Topics in Medicinal Chemistry, 2018)
Nature has been a source of a wide range of products being utilized for the treatment of various diseases like malaria, cancer, diabetes etc. Among these, cancer is emerging as a leading cause of deaths worldwide and the development of cross-resistance to already established drugs increases the need for novel anticancer drugs. To discover novel anticancer molecules, it is a necessity to unearth the molecules which can act as anticancer agents. Taking natural products in vision, phytoconstituents like terpenoids, flavones, glycosides and alkaloids might act as a major source of lead molecules. Considering the anticancer prospectives of phytoconstituents, different unknown lead molecules are summarized in this review. The present review highlights the representative studies of plant-based anticancer agents which are classified as per their phytochemical nature. Furthermore, important key points along with important structure-activity relationships points regarding selected lead molecules are also discussed.
Keywords: Anticancer